Assessment of contaminant levels in locally cultivated vegetables using Agra Canal water and its associated health risks - Kumari, Manisha; Shrivastava, Anamika; Shukla, Kartikeya; Sharma, Rajesh (South Eastern European Journal of Public Health, 2024)
The global imperative to address food safety concerns has intensified, particularly concerning the potential contamination of crops through irrigation from Canal water.Soil samples were analyzed from Faridabad's agriculture site (S3). Tomato, Radish, and Spinach plants were selected for the experiment. Three water ratios were used: the first set of each plant was rinsed with 100%groundwater(GW), the second set of water was irrigated by mixing50% groundwater and 50% canal water(50% GW + 50% CW) and the thirdset was rinsed with 100% canalwater (CW)to determine the effect of water on Plant growth and yielding.Edible parts of harvested vegetables were evaluated for heavy metals.The best growth and yield in spinach and tomato were found in mixed water, while in radish, the best growth was in groundwaterThe highest metal accumulation factor(MAF)was obtained in 100% CW, then in 50% GW + 50% CW irrigated, followed by canal-side and none in 100% GW samples. On the canal side, 41.7% of samples, from 50% GW + 50% CW irrigated vegetables,50% of samples, and 100% CW samples, 83.3% had MAF >1. Health Risk Assessment(HRI) for Pbwas obtained more than 1in 50% GW+50% CWand in 100% CW-raisedveggies and for As incanal-side radishes. The health risk (HI) value was highest in canal water. However, mixed water irrigated veggies were good in yielding and production, but they are unsafe for human health based on MAF, HRI, and HI. This underscores the need for stringent monitoring and regulation to ensure the safety of vegetables for human consumption. The urgency and importance of this issue cannot be overstated. This research will be helpful for farm managers and policymakers.